2006
DOI: 10.1016/j.euje.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pulmonary vascular responses in patients registered with a systemic autoimmunity database: Pulmonary Hypertension Assessment and Screening Evaluation using stress echocardiography (PHASE-I)

Abstract: Stress echocardiography is a useful tool in identifying individuals with autoimmune disease who may have underlying pulmonary arterial disease that may be amenable to therapy. We noted a consistent elevation in sPAP across all autoimmune subtypes, suggesting an abnormal pulmonary vascular response to exercise exists in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 36 publications
1
43
0
4
Order By: Relevance
“…It is difficult to treat symptomatic advanced PAH; therefore, early detection of PAH by a sensitive method is important. Annual cardiac echocardiography or exercise echocardiography is recommended for the detection of early-stage PAH (12,13). The present case showed that 6-minute walk stress echocardiography was a sensitive procedure for detection of PAH; therefore, patients at high risk for PAH such as those with SSc should undergo 6-minute walk stress echocardiography not only for evaluation of exercise capacity but also for detection of early-stage PAH, even if their resting pulmonary arterial pressure is normal.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to treat symptomatic advanced PAH; therefore, early detection of PAH by a sensitive method is important. Annual cardiac echocardiography or exercise echocardiography is recommended for the detection of early-stage PAH (12,13). The present case showed that 6-minute walk stress echocardiography was a sensitive procedure for detection of PAH; therefore, patients at high risk for PAH such as those with SSc should undergo 6-minute walk stress echocardiography not only for evaluation of exercise capacity but also for detection of early-stage PAH, even if their resting pulmonary arterial pressure is normal.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal exercise physiology has been recognized in SSc, idiopathic PAH, idiopathic pulmonary fibrosis (IPF), and chronic obstructive pulmonary disease (21,28,(34)(35)(36)(37)(38)(39)(40). Studies have described exerciseinduced PH in 46-59% of patients with scleroderma spectrum disorders, characterized by Doppler echocardiogram pulmonary artery systolic pressure Ͼ40 mm Hg during exercise (23,41,42). Collectively, these studies suggest an abnormal phenotype in "at-risk" populations after assessing the response of the pulmonary vasculature to exercise.…”
mentioning
confidence: 99%
“…18,19 It has also been used as a screening tool for exerciseinduced pulmonary hypertension in scleroderma 20,21 and in relatives of patients with PAH. 22,23 In addition, Ex-echo has been used in cases chronic thrombo-embolic pulmonary hypertension.…”
Section: Clinical Application Of Exercise Echocardiography In Pulmonamentioning
confidence: 99%